Water quality assessment of effluents from shrimp ponds farming - Nurul Syahida, Harun (2019)
Shrimp aquaculture has become lucrative venture in many of countries in Asia. Water from the shrimp farm contained various substances which can contaminate the water that is resulting from overfeeding to the shrimp, antibiotics or other medicine used to protect shrimp, nutrients and suspended solids. Therefore, the objective of this study is to characterize the water quality of effluent and to be compared with the standard. Water sample were collected from at the point where the water was discharged from the ponds. Analysis of parameters include water temperature, pH, dissolved oxygen, turbidity, total dissolved solids, total suspended solids, biological oxygen demand, chemical oxygen demand, and ammoniacal nitrogen. The result shows all the parameters analysed were below the standard limit.